Non-geometric pulse: An adaptive geometricity approach for Genetic Algorithms - Ferreira, José Pedro Mendes Ribeiro do Vale (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science